Effect of phenylacetamide isolated from lepidium apetalum on myocardial injury in spontaneously hypertensive rats and its possible mechanism. (1st January 2020) - Zhang, Qi; Yuan, Peipei; Li, Meng; Fu, Yang; Hou, Ying; Sun, Yaping; Gao, Liyuan; Wei, Yaxin; Feng, Weisheng; Zheng, Xiaoke
Abstract: Context: In the antihypertensive study of phenylacetamide (PA) on spontaneously hypertensive rats (SHR), it was occasionally found that PA prevents myocardial injury. Objective: Clarify the protective mechanism of PA on myocardial injury in SHR rats. Materials and methods: In vivo, SHR rats were treated with or without PA (15, 30, 45 mg/kg) for 3 weeks (12 per group). In vitro, H9c2 cells were treated with PA (1, 5, 10 μM) for 24 h, and then stimulated with H2 O2 (300 μM) for 4 h. Molecular mechanisms were explored through cardiac pathology, cardiac function and biochemical markers. Results: In vivo, PA (15, 30, 45 mg/kg) reduced CVF from 14.8 ± 1.62 to 9.94 ± 1.56, 8.6 ± 1.33, 8.14 ± 1.45%; increased the LVEF relative level from 0.8 ± 0.06 to 0.83 ± 0.04, 0.86 ± 0.05, 0.9 ± 0.04. All three doses can improve the cardiac pathological structure and function (LVEDD, LVESD, LVFS, heart index, NT-proBNP, CKMB, SBP); however, 45 mg/kg works best. But different doses show different molecular mechanisms. PA (15 mg/kg) improves RAAS system (REN, ACE), inflammation (ET-1, IL-1β) and MAPK pathway (p-ERK/ERK, p-JNK/JNK) better. PA (45 mg/kg) improves oxidative stress (SOD, NOX1) and TGF-β pathway (Smad3) better. In vitro, PA improved cell viability, oxidative stress (SOD, NOX1) and Smad3 protein expression. Discussion and conclusions: PA regulates different mechanisms at different concentrations to improve myocardial injury, and high dose is the best. This experiment provides a theoretical basis for the development of new clinical drugs for cardiovascular disease.